Selective Harmonics Elimination PWM (SHEPWM)Using Differential Evolution Approach - Bahari, Norhazilina (2010)
This paper proposes the application of Differential Evolution (DE) algorithm to the selective harmonics elimination pulse-width modulation (SHE-PWM) scheme. The aim is to solve for the set of transcendental equations that determine the switching angles of the SHE-PWM waveform. The objective function of DE is designed to minimize the selected harmonics to near zero. Furthermore the fundamental component of the output voltage can be controlled independently. To verify the viability of the method, simulation is carried out using MATLAB-simulink. The computed switching angles are applied to a three phase voltage source inverter. Typical results are shown and discussed in relation to the known concepts of SHEPWM.